Annexin-enriched osteoblast-derived vesicles act as an extracellular site of mineral nucleation within developing stem cell cultures - O. G. Davies (Nature Portfolio, 2017)
Abstract The application of extracellular vesicles (EVs) as natural delivery vehicles capable of enhancing tissue regeneration could represent an exciting new phase in medicine. We sought to define the capacity of EVs derived from mineralising osteoblasts (MO-EVs) to induce mineralisation in mesenchymal stem cell (MSC) cultures and delineate the underlying biochemical mechanisms involved. Strikingly, we show that the addition of MO-EVs to MSC cultures significantly (P < 0.05) enhanced the expression of alkaline phosphatase, as well as the rate and volume of mineralisation beyond the current gold-standard, BMP-2. Intriguingly, these effects were only observed in the presence of an exogenous phosphate source. EVs derived from non-mineralising osteoblasts (NMO-EVs) were not found to enhance mineralisation beyond the control. Comparative label-free LC-MS/MS profiling of EVs indicated that enhanced mineralisation could be attributed to the delivery of bridging collagens, primarily associated with osteoblast communication, and other non-collagenous proteins to the developing extracellular matrix. In particular, EV-associated annexin calcium channelling proteins, which form a nucleational core with the phospholipid-rich membrane and support the formation of a pre-apatitic mineral phase, which was identified using infrared spectroscopy. These findings support the role of EVs as early sites of mineral nucleation and demonstrate their value for promoting hard tissue regeneration.